2012
DOI: 10.1007/s11255-011-0098-4
|View full text |Cite
|
Sign up to set email alerts
|

CRP and acute renal rejection: a marker to the point

Abstract: Elevated pretransplant serum CRP level is a risk predictor for acute rejection episodes and may be a useful predictive marker in the follow-up of post-transplantation patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…Consistent with previous clinical studies [9][10][11][12][13], we found that all 75 AKI patients with different causes of disease had elevated levels of serum CRP, which were accompanied by deterioration of renal function. Consistent with previous clinical studies [9][10][11][12][13], we found that all 75 AKI patients with different causes of disease had elevated levels of serum CRP, which were accompanied by deterioration of renal function.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous clinical studies [9][10][11][12][13], we found that all 75 AKI patients with different causes of disease had elevated levels of serum CRP, which were accompanied by deterioration of renal function. Consistent with previous clinical studies [9][10][11][12][13], we found that all 75 AKI patients with different causes of disease had elevated levels of serum CRP, which were accompanied by deterioration of renal function.…”
Section: Discussionsupporting
confidence: 91%
“…Increased serum levels of CRP are also found in patients with AKI and have been suggested as a biomarker of inflammation in AKI [9][10][11][12][13]. Increased serum levels of CRP are also found in patients with AKI and have been suggested as a biomarker of inflammation in AKI [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Limited inflammatory disorders, such as Crohn’s disease, are better managed with the implementation of a regular Hs-CRP measurement (Erlinger et al 2004 ; Owczarek et al 2012 ). Hs-CRP is also useful in determining renal transplant rejection (Grebe et al 2011 ; Roshdy et al 2012 ). A moderate increase in the concentration of Hs-CRP occurs in liver diseases (Komoriya et al 2012 ), autoimmune diseases (Rezaieyazdi et al 2011 ), and neoplasms (Hopkins et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…From the standard markers of inflammation, pretransplant CRP was reported to be a risk factor for acute rejection episodes [ 5 ] or not to influence graft function and survival among children [ 23 ] or adults [ 24 ]. In the present study we also found no influence of pretransplant CRP levels on the rate of delayed graft function or acute rejection and allograft function.…”
Section: Discussionmentioning
confidence: 99%
“…While the immune response shift is well described in the literature, still it is not clear whether the pretransplant chronic inflammation affects posttransplant outcome. From routine blood tests CRP (C-reactive protein) and albumin levels were shown not only to reflect the general immune response in uremic patients [ 3 ] but also to predict kidney outcome [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%